FIGURATIVE LANGUAGE ANALYSIS “IN THE LONELY HOUR” ALBUM BY SAM SMITH - Hulu, Asmenlima (Research on English Language Education, 2024)
This research aimed to know the types of figurative language which are exist in the album "In The Lonely Hour" by Sam Smith and the meaning of the song lyric. This research was designed by using the qualitative method. The source of the data was the album and the data are song lyrics which contain figurative language. Based on the result of the research, it was found 1 Metaphor, 2 personifications, 2 similes, and 5 hyperboles. The total number of figurative language found from the album is ten (10). This implies that the album lacks certain types of figurative language, namely apostrophe, metonymy, synecdoche, understatement, and paradox. The-song “in. the. Lonely. .Hour” Album By. Sam .Smith utilizes figurative language to enhance its beauty and captivate listeners. The chosen figurative-language-carries-profound-meanings within the song's lyrics. Using this song as a teaching tool for semantics, particularly for understanding figurative language, is recommended.